If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -5 = 27y + -90 Reorder the terms: -5 + 10y = 27y + -90 Reorder the terms: -5 + 10y = -90 + 27y Solving -5 + 10y = -90 + 27y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-27y' to each side of the equation. -5 + 10y + -27y = -90 + 27y + -27y Combine like terms: 10y + -27y = -17y -5 + -17y = -90 + 27y + -27y Combine like terms: 27y + -27y = 0 -5 + -17y = -90 + 0 -5 + -17y = -90 Add '5' to each side of the equation. -5 + 5 + -17y = -90 + 5 Combine like terms: -5 + 5 = 0 0 + -17y = -90 + 5 -17y = -90 + 5 Combine like terms: -90 + 5 = -85 -17y = -85 Divide each side by '-17'. y = 5 Simplifying y = 5
| 8x-3(2x+3)=-3 | | x-9y=-2 | | -10=5(w-4) | | 5+7=7+5 | | 10v=-16v+182 | | 12(x+5)=16(x+3) | | 9(l+2)=3(l-3) | | 2x+3(10-x)=25 | | 8+2x=7x-2 | | 15x+73=-347 | | 2(4x-5)-3(-x+6)=2/5(15x-65) | | 8x-12+4=8x-8 | | -5+7x=-4x+39 | | 3x+15+5x=-1 | | 3d^2+7d-6=0 | | 2y=3y-15 | | -3n(4b)+2a(3b)= | | 10x-9=2x-69 | | 8(2x+1)=4x-6x | | 12-6x=5-3+15x | | -5x-5=-5x | | 3(2x-5)=-39 | | 14+2x=-9-5x+4x | | 7g=49 | | y=-1/4+1 | | 3(x+3)=8x+6-5x+3 | | 9-9x=173-37x | | -2/5= | | 3x-12=4x-9 | | 5(2-y)+7y=-3(y+5) | | 3x+8=116 | | -3x+5=-3x+4 |